# 9.2 – Adding & Subtracting Rational Expressions

• View
31

0

Tags:

• #### wrational expressions

Embed Size (px)

DESCRIPTION

9.2 – Adding & Subtracting Rational Expressions. 9.2 – Adding & Subtracting Rational Expressions. Remember adding & subtracting fractions?. 9.2 – Adding & Subtracting Rational Expressions. Remember adding & subtracting fractions? Have to get a common denominator !. - PowerPoint PPT Presentation

### Text of 9.2 – Adding & Subtracting Rational Expressions

• 9.2 Adding & Subtracting Rational Expressions

• 9.2 Adding & Subtracting Rational ExpressionsRemember adding & subtracting fractions?Have to get a common denominator!

• 9.2 Adding & Subtracting Rational ExpressionsRemember adding & subtracting fractions?Have to get a common denominator! 2 _ 3 3 4

• 9.2 Adding & Subtracting Rational ExpressionsRemember adding & subtracting fractions?Have to get a common denominator! 2 _ 3 3 44 . 24 3

• 9.2 Adding & Subtracting Rational ExpressionsRemember adding & subtracting fractions?Have to get a common denominator! 2 _ 3 3 44 . 2 _ 3 . 34 3 4 3

• 9.2 Adding & Subtracting Rational ExpressionsRemember adding & subtracting fractions?Have to get a common denominator! 2 _ 3 3 44 . 2 _ 3 . 3 = 84 3 4 3 12

• 9.2 Adding & Subtracting Rational ExpressionsRemember adding & subtracting fractions?Have to get a common denominator! 2 _ 3 3 44 . 2 _ 3 . 3 = 8 _ 94 3 4 3 12 12

• 9.2 Adding & Subtracting Rational ExpressionsRemember adding & subtracting fractions?Have to get a common denominator! 2 _ 3 3 44 . 2 _ 3 . 3 = 8 _ 9 =4 3 4 3 12 12

• 9.2 Adding & Subtracting Rational ExpressionsRemember adding & subtracting fractions?Have to get a common denominator! 2 _ 3 3 44 . 2 _ 3 . 3 = 8 _ 9 = _ 14 3 4 3 12 12 12

• 9.2 Adding & Subtracting Rational ExpressionsRemember adding & subtracting fractions?Have to get a common denominator! 2 _ 3 3 44 . 2 _ 3 . 3 = 8 _ 9 = _ 14 3 4 3 12 12 12Same w/rational expressions!

• Ex. 1 Simplify each expression

• Ex. 1 Simplify each expressiona. 6 + 8 ab a

• Ex. 1 Simplify each expressiona. 6 + 8 ab a6 + 8 = 6 + ab a ab

• Ex. 1 Simplify each expressiona. 6 + 8 ab a6 + 8 = 6 + 8(b)ab a ab a(b)

• Ex. 1 Simplify each expressiona. 6 + 8 ab a6 + 8 = 6 + 8(b)ab a ab a(b) = 6 + 8b ab ab

• Ex. 1 Simplify each expressiona. 6 + 8 ab a6 + 8 = 6 + 8(b)ab a ab a(b) = 6 + 8b ab ab = 6 + 8b ab

• Ex. 1 Simplify each expressiona. 6 + 8 ab a6 + 8 = 6 + 8(b)ab a ab a(b) = 6 + 8b ab ab = 6 + 8b ab

• Ex. 1 Simplify each expressiona. 6 + 8 ab a6 + 8 = 6 + 8(b)ab a ab a (b) = 6 + 8b ab ab = 6 + 8b abb. m _ 2 m2 4 3m + 6

• Ex. 1 Simplify each expressiona. 6 + 8 ab a6 + 8 = 6 + 8(b)ab a ab a (b) = 6 + 8b ab ab = 6 + 8b abb. m _ 2 m2 4 3m + 6m

• Ex. 1 Simplify each expressiona. 6 + 8 ab a6 + 8 = 6 + 8(b)ab a ab a (b) = 6 + 8b ab ab = 6 + 8b abb. m _ 2 m2 4 3m + 6m (m+2)(m-2)

• Ex. 1 Simplify each expressiona. 6 + 8 ab a6 + 8 = 6 + 8(b)ab a ab a (b) = 6 + 8b ab ab = 6 + 8b abb. m _ 2 m2 4 3m + 6m _ 2 (m+2)(m-2)

• Ex. 1 Simplify each expressiona. 6 + 8 ab a6 + 8 = 6 + 8(b)ab a ab a (b) = 6 + 8b ab ab = 6 + 8b abb. m _ 2 m2 4 3m + 6m _ 2 (m+2)(m-2) 3(m + 2)

• Ex. 1 Simplify each expressiona. 6 + 8 ab a6 + 8 = 6 + 8(b)ab a ab a (b) = 6 + 8b ab ab = 6 + 8b abb. m _ 2 m2 4 3m + 6m _ 2 (m+2)(m-2) 3(m + 2) 3m3(m+2)(m-2)

• Ex. 1 Simplify each expressionb. m _ 2 m2 4 3m + 6m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m 2)3(m+2)(m-2) 3(m+2)(m-2)

• Ex. 1 Simplify each expressionb. m _ 2 m2 4 3m + 6m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m 2)3(m+2)(m-2) 3(m+2)(m-2)

• Ex. 1 Simplify each expressionb. m _ 2 m2 4 3m + 6m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m 2)3(m+2)(m-2) 3(m+2)(m-2) 3m 2(m 2)3(m + 2)(m 2)

• Ex. 1 Simplify each expressionb. m _ 2 m2 4 3m + 6m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m 2)3(m+2)(m-2) 3(m+2)(m-2) 3m 2(m 2)3(m + 2)(m 2)

• Ex. 1 Simplify each expressionb. m _ 2 m2 4 3m + 6m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m 2)3(m+2)(m-2) 3(m+2)(m-2) 3m 2(m 2)3(m + 2)(m 2)3m 2m + 4

• Ex. 1 Simplify each expressionb. m _ 2 m2 4 3m + 6m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m 2)3(m+2)(m-2) 3(m+2)(m-2) 3m 2(m 2)3(m + 2)(m 2)3m 2m + 4 3(m+2)(m2)

• Ex. 1 Simplify each expressionb. m _ 2 m2 4 3m + 6m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m 2)3(m+2)(m-2) 3(m+2)(m-2) 3m 2(m 2)3(m + 2)(m 2)3m 2m + 4 = m + 4 3(m+2)(m2)

• Ex. 1 Simplify each expressionb. m _ 2 m2 4 3m + 6m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m 2)3(m+2)(m-2) 3(m+2)(m-2) 3m 2(m 2)3(m + 2)(m 2)3m 2m + 4 = m + 4 _3(m+2)(m2) 3(m+2)(m2)

Recommended

Documents
Documents
Documents
Documents
Documents
Documents
Documents